DETERMINAN KEMISKINAN DITINJAU DARI VARIABEL PENDIDIKAN DI PROVINSI ACEH - Masro Fitri Ana Harahap; Chenny Seftarita (Jurnal Ilmiah Mahasiswa Ekonomi Pembangunan, 2022)
AbstractPoverty is one of the economic diseases that can reduce people's welfare and education is one of the factors that influence it, for that researchers want to know the effect of education variables on poverty in Aceh Province. The type of research used is descriptive quantitative research with panel data regression method and chooses a random effects model approach (Random Effect). The data used is secondary data, which consists of data on the percentage of poor people, Literacy Rate, Average Years of Schooling, and Expected Years of Schooling which are sourced from the Central Statistics Agency (BPS) of Aceh Province. The results of this study indicate that the Literacy Rate and Average Years of Schooling have a negative and significant effect on poverty, while the Expectation of Years of Schooling has an insignificant negative effect on poverty in Aceh Province in 2016-2020. Local governments need to seek to improve the quality of education through programs that improve the qualifications of educators and ensure that quality educators are distributed evenly in every district/city in Aceh Province. Further research is recommended to add the Main Performance Index (KPI) variable and for the poverty variable to use other indicators such as the Poverty Depth Index and the Poverty Severity Index. .Keywords: Poverty, Literacy Rate, Average Years of Schooling and Expected Years of Schooling